The US Empire, the CIA, and the NGOs (Katehon think tank. Geopolitics & Tradition, 2017)
The CIA recruited the Muslim Brotherhood to fight a proxy war against the Soviet Union in Afghanistan, which led to the withdrawal of the Soviets from the Hindu Kush.